2020
DOI: 10.1111/nph.16982
|View full text |Cite
|
Sign up to set email alerts
|

Root trait–microbial relationships across tundra plant species

Abstract: Fine roots, and their functional traits, influence associated rhizosphere microorganisms via root exudation and root litter quality. However, little information is known about their relationship with rhizosphere microbial taxa and functional guilds. We investigated the relationships of 11 fine root traits of 20 sub-arctic tundra meadow plant species and soil microbial community composition, using phospholipid fatty acids (PLFAs) and high-throughput sequencing. We primarily focused on the root economics spectru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 103 publications
2
40
0
Order By: Relevance
“…(2020) demonstrated that SRL is not positioned on the root conservation gradient but on an independent PC axis related to the ‘collaboration gradient’ that has evolved in concert with symbiosis with mycorrhizal fungi. This novel global conceptualization of belowground trait space has now also been observed in more local and regional studies (Spitzer et al ., 2021; Stock et al ., 2021; Sun et al ., 2021; Sweeney et al ., 2021; Williams et al ., 2021). The key traits along this gradient are mean root diameter (RD) and SRL.…”
Section: An Integrated Framework Of Plant Form and Function – Linking Above‐ And Belowground Traitsmentioning
confidence: 99%
“…(2020) demonstrated that SRL is not positioned on the root conservation gradient but on an independent PC axis related to the ‘collaboration gradient’ that has evolved in concert with symbiosis with mycorrhizal fungi. This novel global conceptualization of belowground trait space has now also been observed in more local and regional studies (Spitzer et al ., 2021; Stock et al ., 2021; Sun et al ., 2021; Sweeney et al ., 2021; Williams et al ., 2021). The key traits along this gradient are mean root diameter (RD) and SRL.…”
Section: An Integrated Framework Of Plant Form and Function – Linking Above‐ And Belowground Traitsmentioning
confidence: 99%
“…Most notably, ‘fast’ species with high specific root length (SRL) may be particularly susceptible to fungal pathogens (Bergmann et al., 2016; Cortois et al., 2016). Recent studies have included a larger suite of root traits, to further explore how root anatomy, morphology, chemistry and physiology influence plant interactions with soil microbes and broad groups of soil fauna (Leff et al., 2018; Moreau et al., 2015; Spitzer et al., 2021; Wilschut et al., 2019). However, in most cases root traits only explained a small portion, if any, of the variation in associated soil communities.…”
Section: Biological Resolution Perspectives On Plant‐soil Feedbacksmentioning
confidence: 99%
“…For example, Sweeney et al (2021) found that temperate grassland plant functional traits, especially root traits, affect the composition of the rhizosphere fungal community and can be used to predict the fungal community. Similarly, Spitzer et al (2021) found that the spectrum of subarctic tundra meadow plants' fine root economic trait chemical axis is positively correlated with the rhizosphere fungus/bacteria ratio. Although many studies have focused on the relationship between root traits and rhizosphere soil microbes [12,[14][15][16][17][18][19][20], no studies we are aware of have explored these relationships in a high-altitude tropical forest ecosystem.…”
Section: Introductionmentioning
confidence: 89%
“…The studies of Zhao [23], Glassman [24] and other scholars [25][26][27][28] mentioned above also showed similar results. Plant roots and rhizosphere soil microorganisms are closely connected, and fine roots and their functional traits affect rhizosphere microorganisms through root exudates and litter quality [13]. The function of specific metabolites in root exudates is indicative of the characteristics of the root economic spectrum, which includes the plant root functional traits.…”
Section: Impact Of the Soil Environment On The Microbial Diversity Of...mentioning
confidence: 99%
See 1 more Smart Citation